Fatwa Haram Perkawinan Beda Agama Kajian Metodologis MUI - Muh. Baehaqi; Muslih (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2023)
Family Law Program, Faculty of Islamic Law, Nahdlatul Ulama Islamic Institut (INISNU), Temanggung. This thesis discusses the prohibition of interfaith marriage, which has become a complex issue in society, with an increasing number of such marriages occurring day by day. It delves deeply into the methodology employed by the Indonesian Ulema Council (MUI) in establishing the fatwa prohibiting interfaith marriages. Furthermore, it explores the evidences and references used by the Indonesian Ulema Council (MUI) in formulating the fatwa on the prohibition of interfaith marriage. According to the MUI's fatwa, interfaith marriage is considered forbidden and invalid, particularly marriages between Muslim men and women from the People of the Book, as per the Qaul Mu'tamad.